Map of North America : engraved to illustrate Mitchell's school and family geography. - Young, J. H. (James Hamilton) (S. Augustus Mitchell, 1852)
Map shows mid-nineteenth century cities and physical features in the United States, Russian America [Alaska], British America, Mexico, Central America, the West Indies, and Greenland; post-Gadsden Treaty boundary between U.S. and Mexico; areas of Native American habitation; Antarctic continent with discovery dates and explorers' names on verso. Relief shown by hachures. Relief shown by hachures and spot heights on verso. Scale [ca. 1:35,000,000].